2019
DOI: 10.3390/cryst9020103
|View full text |Cite
|
Sign up to set email alerts
|

Design of Polarization Splitter via Liquid and Ti Infiltrated Photonic Crystal Fiber

Abstract: We propose a new polarization splitter (PS) based on Ti and liquid infiltrated photonic crystal fiber (PCF) with high birefringence. Impacts of parameters such as shape and size of the air holes in the cladding and filling material are investigated by using a vector beam propagation method. The results indicate that the PS offers an ultra-short length of 83.9 μm, a high extinction ratio of −44.05 dB, and a coupling loss of 0.0068 dB and at 1.55 μm. Moreover, an extinction ratio higher than −10 dB is achieved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…It can be observed from Figure 16 Table 2 presents a comparison of the simulation results between the DC-PCF PBS and other reported DC-PCF PBSs. By observing Table 2, it is maximum ER values in references [12,14,[35][36][37] are all higher than those wit However, it is worth noting that the operational bandwidth of PCF PBS refe length range where ER is greater than 20 dB, while in some studies, the ope width may only exceed 10 dB [12,38] or 15 dB [36]. Therefore, even if the value at a certain wavelength is high, the final spectral bandwidth may not the widest.…”
Section: Simulation Results and Discussionmentioning
confidence: 90%
“…It can be observed from Figure 16 Table 2 presents a comparison of the simulation results between the DC-PCF PBS and other reported DC-PCF PBSs. By observing Table 2, it is maximum ER values in references [12,14,[35][36][37] are all higher than those wit However, it is worth noting that the operational bandwidth of PCF PBS refe length range where ER is greater than 20 dB, while in some studies, the ope width may only exceed 10 dB [12,38] or 15 dB [36]. Therefore, even if the value at a certain wavelength is high, the final spectral bandwidth may not the widest.…”
Section: Simulation Results and Discussionmentioning
confidence: 90%
“…This design is known as multicore photonic crystal fibres (MPCFs), which depend on the coupling behaviour between cores [5]. These MPCFs have been recently implemented in various applications for identical cores, such as couplers [18][19][20][21][22][23][24], power splitters [25][26][27][28], couplers based on high birefringence [29,30], and sensors [16,[31][32]. Non-identical cores, it can also be used in the alloptical logic operation [33], coupling [34], mode selective couplers [35], zero-differential group delay [36], high power lasers [37], polarisation splitters [38], tunable mode converter devices [39], and multiplexers and de-multiplexers [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, developments have revealed that multicore photonic crystal fiber [12], which has attracted interest from researchers for the flexibility of its design, easy manufacturing process, and many research interests are shown towards MPCF couplers [7], the coupling properties of MPCF with adjacent identical cores, useful for coupling [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], splitter [16], switching [17][18]. Besides, it possesses the possibility of realizing a multiplexerdemultiplexer (MUX-DEMUX) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, one can happen difference between the cores of PCF and become non-identical; either by using different index profile, or by using different dimensions, causing changing in refractive index distribution, and this leads to a unequal power distribution in the core of MCPCF. The MPCF coupler with nonidentical cores can also be used for coupling [8,12,19,20], switching [17], and to achieving equal group velocities for different cores to reduce intermodal dispersion [20].…”
Section: Introductionmentioning
confidence: 99%